Los derechos fundamentales en el ciberespacio - Núñez Robinson, Rodolfo (Pontificia Universidad Católica del Perú, 2025)
Fundamental rights must evolve to address the challenges of the contemporary digital environment. Building on the constitutional recognition of unenumerated rights, this work supports the existence of a fourth generation of human rights, centred on interconnectivity and the inherent risks and threats of cyberspace. Cybersecurity is presented not merely as a technical issue, but as a structural condition for the effective exercise of both traditional and emerging fundamental rights. This paper examines cyber threats and risks, emphasizing the need for a comprehensive risk management approach to safeguard individuals and their digital environment. It then identifies new fundamental digital rights: digital existence, digital identity, digital honour and reputation, digital freedom and responsibility, privacy, anonymity, the right to be forgotten, digital domicile, and the right to peace in cyberspace. Each is analysed from a constitutional, technical, and social perspective, highlighting its core content and the corresponding duties of both the State and private actors. The article concludes that in a hyperconnected society, the law cannot remain static. Protecting human dignity requires adapting the constitutional framework to the digital environment, recognizing and guaranteeing fourth-generation rights as essential tools to preserve individual freedom, autonomy, and well-being in cyberspace.

Los derechos fundamentales deben evolucionar para responder a los desafíos del entorno digital contemporáneo. Partiendo del reconocimiento constitucional de los derechos innominados, se concuerda con la existencia de una cuarta generación de derechos humanos, centrada en la interconectividad y los riesgos y amenazas inherentes al ciberespacio. La ciberseguridad se presenta no solo como una cuestión técnica, sino como una condición estructural para el ejercicio de los derechos fundamentales tradicionales y emergentes. En este trabajo se examinan amenazas y riesgos cibernéticos, detallando la necesidad de un enfoque integral de gestión que proteja al individuo y su entorno digital. A partir de ello, se identifican nuevos derechos fundamentales digitales: existencia digital, identidad digital, honor y reputación digital, libertad y responsabilidad digital, privacidad, anonimato, olvido, domicilio digital y el derecho a la paz en el ciberespacio. Cada uno es analizado desde una perspectiva constitucional, técnica y social, destacando su contenido esencial y las obligaciones del Estado y los privados. El artículo concluye que, en una sociedad hiperconectada, el Derecho no puede permanecer estático. La protección de la dignidad humana exige adaptar el marco constitucional al nuevo entorno digital, reconociendo y garantizando los derechos de cuarta generación como herramientas indispensables para preservar la libertad, autonomía y bienestar del individuo en el ciberespacio.
Fundamental rights in cyberspace
Keywords: Cybersecurity; Interconnectivity; Fourth generation rights; Constitutional rights; Cyberspace; Ciberseguridad; Interconectividad; Derechos de cuarta generación; Derechos constitucionales; Ciberespacio; https://purl.org/pe-repo/ocde/ford#5.05.01